Esensi Bantuan Pemerintah Kabupaten Badung Terhadap Keberdayaan Masyarakat - Suartha, Nyoman (PIRAMIDA, 2012)
Community empowerment is a concept that summarizes the economic development of social values. This concept reflects the new development paradigm, namely "people centered, participatory, empowering, and sustainable". This concept is broader than merely satisfy basic needs or provide a mechanism to prevent further impoverishment (safety net), whose thinking recently been developed as an effort to find an alternative to the concepts of growth in the past. Empowerment aims to encourage the community that is still below the poverty line by collectively involved in the decision-making process, including overcoming the unsatisfied condition that there are filled. Empowerment was also marked by the increasing capacity of the population collectively in managing development organizations independently
Keywords: community empowerment; goverment assistance; poverty line